Study on a Novel Cylindrical Gear Which Can Be High-efficiently Machined with the Continuous-index Milling Method - Tang Pei; Wang Le; Ren Shaoying; Li Shanshan (Jixie chuandong)
A kind of cycloidal cylindrical gear is presented in this study. Unlike conventional cylindrical gears, the shape of the tooth profile of this gear in its axial direction is a cycloid. This cycloid gear has the characteristics of large bearing capacity, smooth transmission and no axial force in performance. It adopts the method of continuous-index processing, which greatly improves the processing efficiency. The cycloidal cylindrical gear is machined with a disc milling cutter, and the disc milling cutter is equipped with replaceable blades. The same modulus gear can be machined with only one disc cutter. By replacing the blade, different modulus gear can be machined with the same disc cutter. Firstly, based on the gear meshing theory, the mathematical model of the cycloidal gear was deduced, the discrete tooth surface points were generated by the self-developed calculation software, and three-dimensional models were built. Then, the geometric design of the disc cutter and the processing principle of the cycloidal gear were also introduced. Finally, a calculating table for determining processing parameters was given. This research provides a new idea and basis for the design and machining of cylindrical gears.